The Effect Of Implementing E-Procurement And Internal Control On Prevention Fraud Procurement Of Goods And Services In Bengkulu Government Agency With Moderation Of Organizational Ethical Culture - NovitaSari; Sabrina Fania (UNIB Press, 2025)
This study aims to examine the effect of the application of e-procurement and internal control on the prevention of fraud in the procurement of goods and services in Bengkulu government agencies moderated by organizational ethical culture. The population of this study is the Goods and Services Procurement Work Unit of Bengkulu City and Province, using the total sampling or census method, where the entire population is taken as a sample. This research uses a quantitative approach by collecting primary data using a questionnaire distributed to 33 respondents. The data analysis technique uses census / total sampling. This research was tested using the Moderate Regression Analysis (MRA) test with the SPSS 25 for windows program. The results showed that (1) e-procurement has a positive effect on fraud prevention in the procurement of goods and services, (2) internal control has a positive effect on fraud prevention in the procurement of goods and services, (3) organizational ethical culture can moderate the relationship between e-procurement and government procurement of goods and services, (4) organizational ethical culture is unable to moderate the relationship between internal control and fraud prevention in the procurement of goods and services. This research can be used as input for employees at the good and services procurement work units in the city and province of Bengkulu to get how the influence implementing E-procurement, internal control and organizational ethical culture so that it will improve employees performance and organizational goals can be achieved properly.